Differences in regional gray matter volume predict the extent to which openness influences judgments of beauty and pleasantness of interior architectural spaces. Issue 1 (3rd September 2021) - Skov, Martin; Vartanian, Oshin; Navarrete, Gorka; Modroño, Cristian; Chatterjee, Anjan; Leder, Helmut; Gonzalez‐Mora, José L.; Nadal, Marcos
Abstract: Hedonic evaluation of sensory objects varies from person to person. While this variability has been linked to differences in experience, little is known about why stimuli lead to different evaluations in different people. We used linear mixed‐effects models to determine the extent to which the openness, contour, and ceiling height of interior spaces influenced the beauty and pleasantness ratings of 18 participants. Then, by analyzing structural brain images acquired for the same group of participants, we asked if any regional gray matter volume (rGMV) covaried with these differences in the extent to which the three features influence beauty and pleasantness ratings. Voxel‐based morphometry analysis revealed that the influence of openness on pleasantness ratings correlated with rGMV in the anterior prefrontal cortex (Brodmann area (BA)‐10), and the influence of openness on beauty ratings correlated with rGMV in the temporal pole (BA38) and cluster, including the posterior cingulate cortex (BA31) and paracentral lobule (BA5/6). There were no significant correlations involving contour or ceiling height. Our results suggest that regional variance in gray matter volume may play a role in the computation of hedonic valuation and account for differences in the way people weigh certain attributes of interior architectural spaces. Abstract : We calculated the extent to which contour, ceiling height, and openness influenced beauty and pleasantness evaluations of interior architectural spaces. Our exploratory results demonstrated that the extent to which openness influenced pleasantness evaluations was correlated with regional gray matter volume (rGMV) in the anterior prerontal complex and that the extent to which openness influenced beauty evaluations was correlated with rGMV in the temporal lobe, posterior cingulate complex, and paracentral lobule. Based on our findings, future interventionist approaches employing TMS and/or tDCS could probe the precise computational roles that the regions identified here play in the aesthetic evaluation of architectural interiors.